Deleuze: una ontología, una ciencia - Ramírez Herrera, Gonzalo (2016)
This paper has two objectives: first, to rebut three misconceptions about the philosophy of Gilles Deleuze that deal with his position in ontology, aestheticsand science; and second, to probe deeper into two of these misunderstandings inorder to discover their current scope. Both of these misunderstandings regard hisviews on ontology and on science. Here we will see how an ontology of differenceand an intensive science arise. We will close our paper with some comments on theactuality of this thought.